Persepsi Mahasiswa Sastra Inggris UIN Sunan Kalijaga Yogyakarta terhadap Radikalisme Beragama - Febri Widiandari; Imam Muhsin; Sabarudin Sabarudin (ISLAMIKA, 2023)
Radicalism comes from the Latin radix, meaning "roots", which is an ideology that requires major changes and reforms to progress. Radicalism has become a transnational movement that has penetrated into various countries that are considered strategic by its adherents. Radicalism is very dangerous if it has spread in universities. The purpose of this study was to find out how the perceptions of English Literature students at UIN Sunan Kalijaga Yogyakarta towards Religious Radicalism. This research is a qualitative research using a survey approach. Data collection techniques that researchers use are observation, interviews and questionnaires. The results of this study indicate that students have a good understanding of religious radicalism. Students know and are aware that the actions of radicalism are not synonymous with Islam, realize that it is permissible to work with people outside of Islam, and are aware of the need for students to spread radicalism.